1988
DOI: 10.1063/1.341579
|View full text |Cite
|
Sign up to set email alerts
|

WxN1−x alloys as diffusion barriers between Al and Si

Abstract: Reactively sputtered tungsten nitride (WxN1−x) layers are investigated as diffusion barriers between Al overlayers and Si shallow n+ -p junctions. Both amorphous W80 N20 and polycrystalline W60 N40 films were found to be very effective in preserving the integrity of the n+ -p diodes for 30-min vacuum annealing up to 575 °C. Diode failure at higher temperatures is caused by localized penetration of Al into 〈Si〉 through the WxN1−x barriers. The effectiveness of the barrier decreases for polycrystalline W90 N10 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 6 publications
1
12
1
Order By: Relevance
“…3). This is in agreement with previous reported results, 8,10 where the crystallite structure favors sputter-deposited films whose composition is in the vicinity of W 2 N. However, at a low growth temperature of approximately 150°C used in the present study atomic displacement, local atomic arrangements, and enhancement of adatom mobilities are limited. Thus, the diffraction peaks observed in XRD -2 measurements are broader and their intensities are relatively weak for the WN 0.33 film (compared with the annealed film in Fig.…”
Section: B Film Structure and Stress Relaxationsupporting
confidence: 94%
See 1 more Smart Citation
“…3). This is in agreement with previous reported results, 8,10 where the crystallite structure favors sputter-deposited films whose composition is in the vicinity of W 2 N. However, at a low growth temperature of approximately 150°C used in the present study atomic displacement, local atomic arrangements, and enhancement of adatom mobilities are limited. Thus, the diffraction peaks observed in XRD -2 measurements are broader and their intensities are relatively weak for the WN 0.33 film (compared with the annealed film in Fig.…”
Section: B Film Structure and Stress Relaxationsupporting
confidence: 94%
“…4,5 These oxygen impurities stuff grain boundaries and block the rapid diffusion paths for other atoms such as aluminum and silicon, thus improving the thermal stability of nitride diffusion barriers. However, the preparation and investigation of tungsten nitrides (WN x ) [6][7][8][9][10] are not as intensive as TiN. Moreover, the effect of oxygen on the properties of WN x films remains almost totally unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Between these two extremely different patterns, the five XRD patterns of nanolayer coatings, corresponding to value from 25 to 31 nm, showed apparently gradual change from strongly amorphous structure to nanocrystalline structure. For being widely used in optical and microelectronic applications, many researchers, such as Uekubo et al (1996), Park et al (1997) and Suh et al (1999), have extensively studied and characterized monolayer WNy coatings regarding crystal structure with respect to nitrogen content: Firstly, crystalline structure and nitrogen content of WNy are closely related to deposition conditions, such as nitrogen partial pressure, sputtering power (So et al, 1988), target dc bias voltage, and deposition and post-treating temperature (Volders et al, 2007), etc. For example, with target dc bias voltage varying from −100 to −500 V, Migita et al (2001) found that the sequential changes are achieved from the WN phase with (1 0 0) plane, W 2 N phase with (1 1 1) and (2 0 0) planes, and finally to the amorphous phase.…”
Section: Resultsmentioning
confidence: 99%
“…Since the microstructure affects the extension of active TPB, as a consequence, it determines the overall reaction rate [8][9][10]. On the other hand, electrodes should have high electronic conductivity, good chemical/thermal stability and high catalytic activity also for the dissociation of oxygen molecules [11][12][13][14]. Platinum group metals [15], Ni [16] and lanthanum strontium manganite (LSM) [17] could satisfy these requirements.…”
Section: Introductionmentioning
confidence: 99%